2005
DOI: 10.1097/01.mpa.0000175180.70539.b6
|View full text |Cite
|
Sign up to set email alerts
|

Certain Background Factors Exhibit an Association With an Increased Risk for Pancreatic Calcification Among Japanese Male Alcoholics

Abstract: Drinking behavior, smoking status, and genetic backgrounds are associated with PC and are likely to increase the risk for alcoholic chronic pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…In addition, Nakamura et al [17] found that alcoholics with the (TG)12 allele had a greater risk of presenting pancreatic calcifications on helical computed tomography examination than those with the (TG)11 allele.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Nakamura et al [17] found that alcoholics with the (TG)12 allele had a greater risk of presenting pancreatic calcifications on helical computed tomography examination than those with the (TG)11 allele.…”
Section: Discussionmentioning
confidence: 99%
“…Other genes, such as those encoding detoxifying enzymes (alcohol dehydrogenase (ADH) [17,31] , aldehyde dehydrogenase (ALDH) [17] , glutathione S-transferase (GST) [32] and uridine 5 -diphosphate glucuronosyltransferase (AGT1A7) [33] ) and the transforming growth factor TGFbeta1 [34] might have a role, possibly with an indirect mechanism, in the genetic predisposition to alcoholic pancreatitis. However, the present results do not provide a definite conclusion.…”
mentioning
confidence: 99%
“…This past year, investigators reported gene polymorphisms affecting the immunological response [26][27][28][29] or endogenous/xenobiotic detoxification [30][31][32], but we do not discuss these because of recent reviews of these topics [2,33 ]. This past year, investigators reported gene polymorphisms affecting the immunological response [26][27][28][29] or endogenous/xenobiotic detoxification [30][31][32], but we do not discuss these because of recent reviews of these topics [2,33 ].…”
Section: Major Genetic Forms Of Chronic Pancreatitismentioning
confidence: 99%
“…43,51,[83][84][85][86] Likewise, ADH1B*2 was more prevalent in people with alcoholism who had pancreatitis than those who did not have this complication in some studies but not in others. 84,[87][88][89][90][91] ADH1B has also been studied in relation to certain cancers. Again, many studies have identified ADH1B*2 as a protective factor.…”
Section: -80mentioning
confidence: 99%